A microcalorimetric analysis of quinoa seeds with different initial water content during germination at 25°C - Sigstad, Emma Elizabeth (2001)
Quinoa (Chenopodium quinoa Willd.) is an ancestral crop from the Andes of South America. Its high-energy and nutritional value content makes this crop very suitable for food. Germination of quinoa seed remains a problem. In the present work germination of quinoa seeds with different initial moisture contents were monitored by microcalorimetry at 25°C. Storage at moisture contents above 0.082 g g-1 drastically reduces seed germination.